Creative Economy-Based Cultural Tourism Through Sustainable Tourism in Kampung Batik Okra Surabaya - Ratih Mukti Azhar; Daisy Marthina Rosyanti; Ayundha Evanthi; Ilham Hardi; Shabrina Aulia A. (Future Science, 2023)
The emerging tourist spot of Kampung Batik Okra Surabaya requires assistance for its development. Specifically, the community seeks support in enhancing the village's image as a tourist destination and leveraging social media for promotional purposes. Our team aims to facilitate this development by providing expertise on e-branding strategies to bolster the village's presence and appeal to a broader tourist audience. Additionally, we aim to enhance their social media proficiency and create product catalogs to better understand production capabilities and market demands. Through these efforts, aim to establish Kampung Batik Okra as a compelling tourist destination, emphasizing its uniqueness, beauty, authenticity, and sustainability. Our objectives include improving the village's branding through catalog and pamphlet creation, thus increasing its visibility and attractiveness to visitors. The objectives of this initiative are as follows: (1) Enhancing the visibility of Batik Okra Surabaya village through the creation of catalogs and pamphlets, as well as providing training in photography and videography for promotional purposes. Additionally, strengthening the village's presence through e-branding strategies utilizing social media platforms. (2) Facilitating knowledge transfer regarding the effective use of social media for promoting tourism in Kampung Batik Okra Surabaya. The anticipated outputs of these efforts include: (1) Improved branding through an e-branding approach capable of reaching a wider audience of tourists. (2) Enhanced proficiency in utilizing social media platforms for tourism promotion.